Design and Implementation of a Microcontroller-Based Air Filter System with Android Application Interface - Muhammad, Kusban; Ramadhan Putra, Rafigo; Purnomo, Eko (Emitor: Jurnal Teknik Elektro, 2026)
Indoor air quality is a crucial factor influencing occupants’ health and comfort. Various issues, including dust particles, excessive humidity, hazardous gases, and inadequate lighting conditions, can significantly reduce indoor air quality. However, most existing air filter systems still lack real-time monitoring and remote control capabilities. Therefore, this study aims to develop a microcontroller-based air filter system using ESP32 integrated with an Android application via Wi-Fi connectivity. The proposed system utilizes a DHT22 sensor to measure temperature and humidity, a GP2Y1010AU0F sensor to detect dust particles, an MQ-135 sensor to detect harmful gases and unpleasant odors, and a BH1750 sensor to measure light intensity. All sensor data are processed by the ESP32 microcontroller and displayed through an Android application developed using Android Studio, allowing users to monitor indoor air quality conditions in real time. System testing was conducted under several indoor air quality scenarios, including variations in humidity and dust concentration levels. The results demonstrate that the system operates accurately, responsively, and in real time in monitoring indoor air quality. Furthermore, the system can be remotely controlled through the Android application. This system is expected to improve indoor air quality while providing positive impacts on environmental health and comfort.